Bing chat: toward a new way of understanding searches - Lopezosa, Carlos (Anuario ThinkEPI, 2023)
On February 7, 2023, Microsoft announced the launch of a new Bing search engine that integrates artificial intelligence (AI) in the form of a chat to enhance the search experience. This work presents a basic functional analysis of this search engine and proposes a series of reflections on the effect of AI on search engines, both from the point of view of users as well as from the perspective of researchers in the field of documentation and communication who are dedicated to the study of web visibility and information retrieval.